2009
DOI: 10.1080/00365510802699246
|View full text |Cite
|
Sign up to set email alerts
|

Activity of selected enzymes in erythrocytes and level of plasma antioxidants in response to single whole‐body cryostimulation in humans

Abstract: The influence of extremely low temperatures on the human body and physiological reactions is not fully understood. The aim of this research was to estimate the influence of a single exposure to cryogenic temperature (-130 degrees C), without subsequent kinesiotherapy, on the activity of the most crucial antioxidant enzymes in erythrocytes: superoxide dismutase (SOD), catalase (CAT), glutathione reductase (R-GSSG), glutathione peroxidase (GPx) and glutathione transferase (T-GSH). In the plasma, the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…In another study by this team [31], healthy men were exposed to a single WBC session (temperature: -130º C, time: 3 min, two-step cryochamber, liquid nitrogen coolant) without subsequent kinesiotherapy. The authors observed a significant increase in GPx and GR activities, with a simultaneous decrease in CAT and glutathione S-transferase activities.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by this team [31], healthy men were exposed to a single WBC session (temperature: -130º C, time: 3 min, two-step cryochamber, liquid nitrogen coolant) without subsequent kinesiotherapy. The authors observed a significant increase in GPx and GR activities, with a simultaneous decrease in CAT and glutathione S-transferase activities.…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that cryostimulation mobilizes the white blood cells, particularly immunocompetent lymphocytes [4,15,21,22]. The effect on red blood cells has not been positively confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Cryotherapy resulted in decreased levels of testosterone (T) and estradiol (E2) in football players, albeit with no changes in the concentration of luteinizing hormone (LH) and dehydroepiandrosterone (DHEA-S) [18]. Recent reports also suggest a stimulating antioxidative effect of cryostimulation [8,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response of the body to cold temperatures occurs through changes in the endocrine system (increase in adrenocorticotropin concentration, β-endorphins, epinephrine, norepinephrine and testosterone concentration in men) [1][2][3][4], circulatory system (contraction of blood vessels in the skin, then their dilation and congestion of the skin) [5], neuromuscular system (reduction of muscle tension, decrease in nerve conduction velocity) [6] and immunological system (increase in cell-mediated and humoral immunity) [1,[7][8][9][10]. Moreover, whole body cooling influences the prooxidant-antioxidant balance in blood [11][12][13][14], and has an anti-inflammatory [15] as well as an analgesic effect [6]. This analgesic effect is caused by the combination of increased β-endorphin concentration and decreased nerve conduction in afferent fibers, which are responsible for pain reception [2,16].…”
Section: Introductionmentioning
confidence: 99%